Incentives to Save Energy as a Top Priority - Silke Übelmesser (Wirtschaftsdienst)
Abstract To address the distributional consequences of high inflation rates, measures are needed that target those most in need without distorting prices. The function of the price as scarcity signal is important to encourage energy saving. Direct price subsidies such as the fuel price rebate, on the contrary, are not helpful. In the medium term, supply-side measures are needed to overcome the bottlenecks in the supply chains. Other challenges, the impact of demographic change in particular, make this even more urgent. Sound public finances lead to greater resilience. Planning to reintroduce the debt brake is reasonable as the current distributional issues need to be solved within the current generation and not shifted to future ones.